Best Practices in Developing a National Palliative Care Policy in Resource Limited Settings: Lessons from Five African Countries - Luyirika, Emmanuel B.K.; Namisango, Eve; Garanganga, Eunice; Monjane, Lidia; Ginindza, Ntombi; Kiyange, Fatia (Ecancermedicalscience, 2016)
Given the high unmet need for palliative care in Africa and other resource limited settings, it is important that countries embrace the public health approach to increasing access through its integration within existing healthcare systems. To give this approach a strong foundation that would ensure sustainability, the World Health Organisation urges member states to ensure that policy environments are suitable for this intervention. The development, strengthening, and implementation of national palliative care policies is a priority. Given the lack of a critical mass of palliative care professionals in the region and deficiency in documenting and sharing best practices as part of information critical for regional development, policy development becomes a complex process. This article shares experiences with regard to best practices when advocating the national palliative care policies. It also tells about policy development process, the important considerations, and cites examples of policy content outlines in Africa.
Keywords: policy makers, palliative care, palliative care policy, policy development, policy goals, health systems, situational analysis, terms of reference, evidence, government, pain medications, controlled substances, financial resources, stakeholders, consultation